Standardization and in vitro antioxidant activity of jatamansi rhizome - Mhaveer Singh; Mohammad A Khan; Masood S Khan; S H Ansari; Sayeed Ahmad (Wolters Kluwer Medknow Publications, 2015)
Background: Nardostachys jatamansi Linn. commonly known as jatamansi is a well notorious drug in Indian systems of medicines having various health-related benefits and employed in various herbal formulations due to the presence of high levels of valuable phenolic constituents. The present study was aimed to quality assessment of Jatamansi rhizome by studying macro- and micro-scopic characters along with physicochemical tests, chemo-profiling using thin layer chromatography (TLC), and gas chromatography-mass spectrometry (GC-MS), in vitro antioxidant activity. Materials and Methods: Standardization was carried out as per the pharmacopeial guidelines and contaminant estimation was carried out by analyzing the samples for the determination of heavy metals, pesticides, and aflatoxins. Chemo-profiling was done with TLC by optimizing the mobile phase for different extracts. The GC-MS chemo-profiling was also carried out by using hexane soluble fraction of the hydroalcoholic extract. The drug is well known for a protective role in the human body as an antioxidant, so total phenolic contents and in vitro antioxidant efficacy was also determined by using established methods. Results:The results of quality control and anatomical studies were very much useful for its identification, whereas significant antioxidant efficacy was also observed. The drug was found free of contaminants when analyzed for pesticides and aflatoxins, whereas heavy metals were found under the pharmacopeial limit. Conclusion: The findings of the present research can be utilized for the identification and quality control of the jatamansi rhizome.